Evaluation of the Family Planning Programme - Design, Schedules etc. and Instructions - Planning Commission (Planning Commission, 1968)
The evaluation of the Family Planning Prograr.im was undertaken by the P.E.O. in 1963-64 at the instance of the Family Planning Programme Evaluation and Planning Committee appointed by the Ministry of Health. the report was submitted to the Ministry of Health in June 1965. and considered by the Ministry as well as by the Cabinet Sub-Committee.
Programme Evaluation Organisation Planning Commission Government of India